Eksistensi Keindahan Nagari Maligi : “Surga Tersembunyi di Pasaman Barat” - Hambali; Harmi, Hasnaini Hawazi; Zebua, Yunita Gabriella Marselin; Oktaviona, Elza; Febrianti, Indah Dwi; Ananta, Thania (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
Nagari Mailigi, a village in West Sumatra, has extraordinary tourism potential but is not widely known. The main attraction is the enchanting open beach with clean white sand and clear sea water, which presents a spectacular and relaxing natural view. The beauty of this beach offers quite a variety of activities such as enjoying stunning sunrises and sunsets. However, this great potential has not been fully exploited due to limited existing infrastructure. Difficult road access, lack of accommodation facilities, and lack of promotion are the main challenges in developing the tourism sector in Nagari Mailigi. It is hoped that improving infrastructure and effective tourism promotion can open up opportunities for local economic growth, while preserving the environment and local culture. With proper attention and management, Mailigi can become a leading tourist destination that offers authentic and unforgettable natural experiences